Analysis Of Facilities And Service Quality On Loyalty Service Users Of Pt Pelabuhan Indonesia Branch Belawan Mediated By Satisfaction - Budi Rusdianto; Slamet Widodo; Elfitra Desy Surya (Yayasan Multidimensi Kreatif, 2025)
This study aims to test and analyze the influence of facilities and service quality on the loyalty of Indonesian port service users Belawan Branch. To test and analyze the influence of facilities and service quality on the loyalty of Indonesian port service users Belawan Branch through satisfaction. This research is a quantitative research. Sampling technique with purposive sampling. The population is all consumers who use port services as many as 77 populations and are immediately used as a saturated sample. This research was processed using SMART PLS. The results of the study show that facilities have a positive and significant effect on customer satisfaction using PT Pelabuhan Indonesia Belawan Branch port services. The quality of service has a positive and significant effect on customer satisfaction using PT Pelabuhan Indonesia Belawan Branch port services. Satisfaction has a positive and significant effect on customer loyalty using PT Pelabuhan Indonesia Belawan Branch port services. Facilities have a positive and significant effect on customer loyalty using PT Pelabuhan Indonesia Belawan Branch port services. The quality of service has a positive and significant effect on customer loyalty using the port services of PT Pelabuhan Indonesia Belawan Branch. Facilities have a positive and significant effect on customer loyalty using PT Pelabuhan Indonesia Belawan Branch port services through satisfaction. Service Quality has a positive and significant effect on customer loyalty using PT Pelabuhan Indonesia Belawan Branch port services.